Clinical and exercise professional opinion on designing a postpartum return-to-running training programme: an international Delphi study and consensus statement - Deering, R. E.; Donnelly, G. M.; Brockwell, E.; Bo, K.; Davenport, M. H.; De Vivo, M.; Dufour, S.; Forner, L.; Mills, H.; Moore, I. S.; Olson, A.; Mathur, S.; et al. (British Journal of Sports Medicine, 2024)
Returning to running postpartum presents challenges such as musculoskeletal pain and pelvic floor dysfunction for some females, but there is little guidance on developing and progressing postpartum training programmes. This study aims to establish expert consensus recommendations on designing and modifying a postpartum return-to-running training programme, highlight costs and access to qualified professionals as potential barriers and discuss clinical, research and sports policy implications.